Pengaruh Senam Otak Terhadap Kemampuan Pre Writting Skill Pada Anak Autis - Artho, Arief Budhi, Edy Waspada, S.ST.Ft., M.Kes (2017)
This study aims to determine the effect on Ability Brain Gym in enhancing the ability Pre Writting Skill on aspects thicken lines, bold vowels, and copy the vowels in autistic children at the Center for Autism Services. This study was an experimental study with the approach of Single Subject Research (SSR) with the design of the A1-B-A2. The research subject is an autistic child in DIY Autism Services Center, which is the subject of Je. The collection of data by measuring the percentage of achievement of pre writting skills using performance test. Data were analyzed by descriptive statistics and displayed in graphical form. The components were analyzed, namely in the state and inter-state analysis. Based on the results of research on the learning process of pre writting skills during the session interventions showed improvement experienced by the child's ability demonstrated by the increase in the mean scores level on aspects thicken lines, bold vowels. Subjects (Je) to thicken lines mean level increased from 42% at baseline conditions-1 (A1) to 64% at the time of the intervention (B) and 86% at baseline-2 (A2). Subjects (Je) for bold the vowels, the mean level increased by 24% in the baseline condition-1 (A1) to 62% in the intervention (B) and 88% at baseline-2 (A2). Subjects (Je) to copy the vowels, an increase of 24% in the baseline condition-1 (A1) to 68% at the time of the intervention (B) and 80% at baseline-2 (A2). The research shows that through the use of brain exercises, pre writting skills relating to the aspects thicken lines, thicken vowels, and copy the vowels can be increased, thereby can be concluded that use Brain Gym can improve the ability pre writting skill in autism children.